Phase Changes of Light on Reflection from a Dielectric - Batista-Leyva, A. J.; Batista-Tomás, A. R. (Revista Cubana de Física, 2015)
Phase changes of an electromagnetic wave when it is reflected from a plane dielectric is determined using the Fresnel relations and the vector diagrams of E and H . Though these equations are textbook science, their application is troublesome. Here we analyze the use of Fresnel relations to study phase changes by reflection in some of the more often used textbooks of General Physics, both in Cuba and other countries, pointing out some problems present in their analysis. The paper could be useful for professors of Optics and General Physics.